Heavy ion induced electrical property degradation in sub-100 nm bulk silicon MOS devices - 陈叶华 安霞 武唯康 张曜 刘静静 张兴 黄如 (Journal of semiconductors, 2015)
The radiation response of 90 nm bulk silicon MOS devices after heavy ion irradiation is experimentally investigated. Due to the random strike of the incident particle, different degradation behaviors of bulk silicon MOS devices are observed. The drain current and maximum transconductance degrade as a result of the displacement damage in the channel induced by heavy ion strike. The off-state leakage current degradation and threshold voltage shift are also observed after heavy ion irradiation. The results suggest that the radiation induced damage of sub-100 nm MOS devices caused by heavy ion irradiation should be paid attention.